Multidrug-resistant tuberculosis and risk factors associated with its development: a retrospective study - Omar Sald Elmi; Habsah Hasan; Sarimah Abdullah; Mat Zuki Mat Jeab; Zilfalil Bin Alwi; Nyi Nyi Naing (Journal of Infection in Developing Countries)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) has emerged as a major clinical public health threat and challenges the national TB control program in Malaysia. Data that elaborates on the risk factors associated with the development of MDR-TB is highly limited in this country. This study was aimed to determine the risk factors associated with the development of MDR-TB patients in peninsular Malaysia. Methodology: This was a case control study; the data were collected from medical records of all the registered MDR-TB patients at five referral TB hospitals in peninsular Malaysia from January 2010 to April 2014. The 105 cases were all confirmed by a positive sputum culture of Mycobacterium tuberculosis for MDR-TB and extensively drug-resistant (XDR)-TB. As a comparison, a total of 209 non-MDR-TB cases were randomly selected as controls. Results: A total of 105 MDR-TB and 209 non MDR-TB patients were studied. The risk factors associated with MDR-TB within the multivariate analysis were previous tuberculosis treatment, HIV infection, being an immigrant, and high load of positive for acid-fast bacillus (AFB) smear. Conclusions: The findings of this study revealed that patients who had received previous treatment for tuberculosis, were infected with HIV, were immigrants, and had a high burden of positive testing for AFB smear were more likely to have MDR-TB. An enhanced understanding of the risk factors associated with MDR-TB strains is imperative in the development of a national policy for public health interventions.